2014
DOI: 10.1002/emmm.201303281
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 in keratinocytes causes chloracne (MADISH)‐like skin disease in mice

Abstract: The transcription factor Nrf2 is a key regulator of the cellular stress response, and pharmacological Nrf2 activation is a promising strategy for skin protection and cancer prevention. We show here that prolonged Nrf2 activation in keratinocytes causes sebaceous gland enlargement and seborrhea in mice due to upregulation of the growth factor epigen, which we identified as a novel Nrf2 target. This was accompanied by thickening and hyperkeratosis of hair follicle infundibula. These abnormalities caused dilatati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 44 publications
(64 reference statements)
3
96
1
Order By: Relevance
“…1D and Supplementary Fig. S1C), consistent with the enlarged sebaceous glands in mice with stronger Nrf2 activation (3,19).…”
Section: Nrf2 Activation Has a Mild Tumor-preventive Effect In A Modesupporting
confidence: 70%
“…1D and Supplementary Fig. S1C), consistent with the enlarged sebaceous glands in mice with stronger Nrf2 activation (3,19).…”
Section: Nrf2 Activation Has a Mild Tumor-preventive Effect In A Modesupporting
confidence: 70%
“…On mating these mice with transgenic mice expressing Cre recombinase under control of a keratin 5 (K5) promoter, the STOP cassette is deleted in keratinocytes, resulting in expression of caNrf2 in all layers of the epidermis and in the hair follicles. The double mutant mice (designated K5Cre-CMVcaNrf2 mice) develop progressive epidermal thickening and hyperkeratosis as well as enlarged sebaceous glands 9,26 . However, only very minor phenotypic abnormalities are present in neonatal mice 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Total cellular RNA isolation, purification using the MinElute Kit (QIAGEN, Hilden, Germany), cDNA synthesis, and quantitative RT-PCR (qRT-PCR) were described previously (6). Primers used are listed in Table I.…”
Section: Rna Isolation and Quantitative Rt-pcrmentioning
confidence: 99%
“…This causes enhanced drug resistance, increased survival under stress conditions, and hyperproliferation of the tumor cells as a result of an increased abundance of multidrug-resistance proteins, ROSdetoxifying enzymes, and metabolic enzymes (2,3). Recent studies from our laboratory also demonstrated that chronic activation of Nrf2 in keratinocytes causes hyperkeratosis, epidermal thickening due to keratinocyte hyperproliferation, cutaneous inflammation, and sebocyte hyperplasia (4)(5)(6). Therefore, we searched for soluble mediators that are controlled by Nrf2 and may affect cell proliferation and/or inflammation.…”
mentioning
confidence: 98%